Executive Compensation and Tournament Theory: Empirical Tests on Danish Data - Eriksson, Tor (Journal of Labor Economics, 1999)
This article adds to the empirical literature on tournament theory as a theory of executive compensation. I test several propositions of tournament models on a rich data set containing information about 2,600 executives in 210 Danish firms during a 4‐year period. I ask, Are pay differentials between job levels consistent with relative compensation? Is pay dispersion between levels higher in noisy environments? Is the dispersion affected by the number of tournament participants? Is average pay lower in firms with more compressed pay structures? Does wider pay dispersion enhance firm performance? Most of the predictions gain support in the data.